Exploring the strategy modes of military managers - Ozleblebici, Z.; Pinto, C.; António, N. (Journal of Military and Information Science, 2015)
It is evident from the literature that the concept of strategy has been adopted from the military and well modified for use in the business world. However, despite the thousands years old military origin of strategy the previous researches focused on only business managers’ perceptions on strategy. Therefore, in order to address this gap in the literature, the paper intended to identify the strategy modes among military managers. By using factor analysis the study reveals and moreover categorizes five different modes of strategy among the military managers. Practical use of the research findings, limitations, as well as future research directions are also provided.